Sociodemographic risk factors for gestational syphilis in a maternity hospital in Santa Catarina, Brazil - Karoline Bunn Borba; Rosemeri Maurici da Silva (Hospital de Clínicas de Itajubá, 2022)
Objective: to identify risk factors for the acquisition of gestational syphilis. Methods: Coorte study. The participants will perform rapid tests to detect syphilis during pregnancy and hospitalization. Data referring to age, ethnicity, education, and family income were collected in the interview. To investigate factors associated with syphilis infection in the gestational period, binary logistic regression models were run to analyze the crude and adjusted odds ratios for sociodemographic and economic variables. The statistical significance level of 5% was adopted. Results: There was a statistically significant association between syphilis infection and the social class of the patient [χ2 9.821 (4 df); p = 0.05]. The logistic regression model showed that black women had a higher chance of syphilis infection (OR = 2.582; 95% CI 1.068 - 6.243). Conclusion: Low social class and black ethnicity are risk factors for acquiring syphilis during pregnancy.